Characteristics of biopolymer films with essential oils - Jamróz, E. (Polimery, 2021)
This paper provides areview of the literature on the effect of essential oils on the properties of gelatin, chitosan, and gelatin-chitosan films. Biopolymer films are inexpensive, biocompatible and functional, while the modification of biopolymer matrix with antibacterial and antioxidant essential oils makes possible to use the produced films in food packaging instead of synthetic materials.